PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP MINAT MENGGUNAKAN JASA STUDIO OMAHPHOTO BOJONEGORO - Effasa Ahmad Saifurriza; Romadhoni Agus (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
Along with the development of technology especially the internet, more and more social media are popping up so as to encourage the emergence of Electronic Word Of Mouth (e-WOM). Studio Omahphoto is one studio that offers his services to utilize Electronic Word Of Mouth (e-WOM) through social media Instagram. The objectives to be achieved in this research is to find out how the magnitude of the influence of the Electronic Word Of Mouth (e-WOM) against the interests of consumers using service Studio Omahphoto Bojonegoro. This research is quantitative research using Survey Method. The sampling technique used was Purposive Sampling. Data collection was done by disseminating a questionnaire to the 65 respondents with criteria already use the service Studio Omahphoto Bojonegoro and the interpretation of data using Multiple Linear regression analysis. The results showed that the influence of dimensions of Electronic Word of Mouth (e-WOM) against the interests of consumers using service Studio Omahphoto Bojonegoro of 0.722 or 72.2% meaning that effect is very powerful, because it set the value of R is approaching the number one.